SEMANTIC ANALYSIS IN LEXICON MEMBAWA IN BIMANESE - Umar (International Journal of Linguistics and Discourse Analytics, 2020)
The current study attempts to describe the differences meaning of lexicon membawa in Bimanese. The research applied a descriptive qualitative method. The data analyzed by implemented of Leech theory meaning. It divided into seven types of meaning: conceptual, connotative, social, affective, reflective, collocative, and thematic. Based on the data analysis by using collocative meaning show that fourteen lexicons membawa are used by Mbojo ethnic group in daily communication in different context. The lexicons of membawa include tewe [tewe], su’u [su’u], ce’i [ce’i], lemba [lemba], tundu [tundu], geo [geo], pompo [pompo], semba [semba], kapi [kapi], gendo [gendo], peso [peso], congge [congge], ngganta [ngganta], and kalei [kalei].